"A distant mirror": Sensemaking in the era of Trump. (April 2021) - Chace, Sarah; Lynerd, Benjamin T; DeSantis, Adrianna
Sensemaking is an ongoing act of constructing a reality to be interpreted. While numerous articles have explored the notion of sensemaking in organizations, far fewer have examined it through the empirical prism of an individual case of sensemaking, with the notable exception of Weick's seminal contribution and formulation, "The Collapse of Sensemaking in Organizations: The Mann Gulch Disaster" (1993). In this article, we seek to build on the literature of sensemaking in organizations by offering an analysis of the actions of former Republican Senator Jeff Flake, whose leadership interventions we interpret as efforts at sensemaking in the era of Trump. In this context, we focus on the US Senate as an organ of sensemaking established by the framers of the Constitution to be relied upon in times of disruption, confusion, and chaos—a check on presidential power established by the framers of the US Constitution to provide prospective sensemaking for uncharted waters. In analyzing the case of Jeff Flake as sense-maker, we rely on certain definitions of leadership embedded in the era of post-truth. We conclude that Flake's actions may be seen as a distant mirror (to quoteTuchman, 1978 ) of Weick's treatment of the storied smokejumper Wag Dodge—a sense-maker whose persuasive powers failed him in the moment, only to be viewed in retrospect as the one who paved the way forward toward survival in the midst of a "cosmological episode."